A Pilot Study of Fluorescence-Guided Resection of Pituitary Adenomas with Chlorin e6 Photosensitizer - Elizaveta I. Kozlikina; Kanamat T. Efendiev; Andrey Yu. Grigoriev; Olesia Y. Bogdanova; Igor S. Trifonov; Vladimir V. Krylov; Victor B. Loschenov (Bioengineering, 2022)
Fluorescence diagnostics is one of the promising methods for intraoperative detection of brain tumor boundaries and helps in maximizing the extent of resection. This paper presents the results of a pilot study on the first use of the chlorin e6 photosensitizer and a two-channel video system for fluorescence-guided resection of pituitary adenomas. The study’s clinical part involved two patients diagnosed with hormonally inactive pituitary macroadenomas and one patient with a hormonally active one. All neoplasms had different sizes and growth patterns. The data showed accumulation of chlorin e6 in tumor tissues in high concentrations: Patient 1: 2 mg/kg, Patient 2: 5 mg/kg, and Patient 3: 4 mg/kg. For Patient 1, the residual part of the tumor was not resected since it was intimately attached to the anterior genu of the internal carotid artery. For Patients 2 and 3, no regions of increased Ce6 accumulation were detected in the tumor foci after resection. Therefore, the use of the Ce6 and a two-channel video system helped to achieve a high degree of tumor resection in each case.